FOREIGN DIRECT INVESTMENT, RENEWABLE ENERGY AND ECONOMIC GROWTH: AN EMPIRICAL ANALYSIS FROM SOUTH AFRICA - Ahmed Oluwatobi Adekunle (Gusau Journal of Accounting and Finance)
This paper explores the connection amid renewable energy, FDI and economic growth in South Africa using the vector error correction model (VECM) and exogeneity granger causality test. The data employed in this study covered 1990-2020, all obtainable from World development indicator (WDI) and International Energy Agency (IEA). The results revealed that a significant causal connection from economic growth to renewable energy is observed over the long-run while renewable energy does not granger cause economic growth, a uni-directional causality exist amid the economic growth and renewable energy. The study recommends that the government should offer some sort of help to make sure organizations or companies are adequately influenced to depend largely on renewable energy which will facilitate ecological friendly system in the country.